Edukacja bocznych linii rodu Radziwiłłów w XVIII wieku. Wyznacznik statusu społecznego czy szansa na awans? - Mariani, Andrea (Biuletyn Historii Wychowania, 2024)
The paper analyses the education of the members of three collateral lines of the Radziwiłł family (Kleck, Szydłowiec and Berdyczów) between the late 17th century and 1773, the year of the suppression of the Society of Jesus. The author has resorted to various archival sources, particularly private letters and diaries. The decline in social prestige of these family lines determined the way in which their members were educated. While all the members of the first generation studied in various Jesuit colleges and later undertook the grand tour, later on most Radziwiłłs were educated under the supervision of their more powerful relatives from Nieśwież. Nevertheless, they received careful education, often in Jesuit or Piarist colleges for noblemen. Command of modern languages, history and geography favoured their political career during the crisis of the Nieśwież branch in the 1760s. After reconstructing the early life of various members of the Radziwiłł family, the author analyses the criteria that determined the choice of various schools.